ANTI-HISTAMINE ACTIVITY OF AMIRTHA SANJEEVI KULIGAI (PILL) - Sangeetha, D. P.; Banumathi, V.; Ganthimathi, S.; Shameem, F. R. (International Journal of Ayurveda and Pharma Research, 2015)
Many children suffer from recurrent coughing, wheezing and chest tightness. In pre-school, one third of all children have these symptoms before the age of six, but only 40% of these wheezing pre-schoolers will continue to have asthma. In older school-aged children the majority of the children have asthma. Quality of life in childrens is affected by asthma. Sleep disruption and exercised induced airflow limitation have a negative impact on participation in sports and social activities, and may influence family life. In children and young adults asthma is usually accompanied by allergic (atopic) phenomena such as elevation of the total serum immunoglobulin E concentration. Nowadays the management of childhood asthma is commonly with synthetic corticosteroids, but it has some side effects like weight gain, tachycardia, depression, glaucoma etc. In traditional Siddha system of medicine several herbal and herbo mineral formulations are indicated for respiratory problems in paediatric age group. Amirtha Sanjeevi Kuligai is a poly herbal formulation indicated for this disease in Siddha literature. Histamine plays a major role in the pathogenesis of asthma. So, the Anti- histamine activity of Amirtha Sanjeevi Kuligai was carried out by determining the histamine activity of injecting histamine in wister albino rat by hind paw method. The change in the hind paw volume was measured using plethysmometer and expressed as mean paw volume. The study result concluded that the drug Amirtha sanjeevi kuligai has got significant Anti- histamine activity.